The uptake of and structural changes induced by trichloroacetic acid in the needles of scots pine seedlings - Sutinen, S.; Juuti, S.; Koivisto, L.; Turunen, Minna; Ruuskanen, J. (Journal of Experimental Botany, 1995)
The uptake of trichloroacetic acid (TCA) and structural changes induced in the needles of Scots pine (Pinus sylvestris L.) seedlings were studied. Two exposure set-ups, a root route and an atmospheric route through the surfaces simulating the wet deposition of fog, were used. Both set-ups included two dose levels and corresponding control treatments. The temperature and the relative humidity in the climate chambers were adjusted to represent the conditions of June-July in a subarctic area in central Finland. The seedlings were exposed three times a week for two months. The results showed that the uptake of TCA in needles occurred both via roots and via needle surface. However, most of the TCA via the atmospheric route was absorbed on the surface of the needles. The structural responses in pine needles depended partly on the treatment method: TCA applied via the atmospheric route disintegrated the structures of the epicuticular waxes and that of the stomatal cells, which was not seen in the exposures via roots. A common feature was the decrease in size of the chloroplasts in concert with the increasing TCA concentrations inside the needles. © 1995 Oxford University Press.